Structurally characterized one oxo–desoxo bridged Mo2–bis(dithiolene) complex and its interconversion to a discrete oxo or desoxo DMSOR model. (15th May 2019) - Moula, Golam; Bose, Moumita; Sarkar, Sabyasachi
Abstract : The dissymmetric binuclear complex1 acts as a precursor of the molybdoenzyme models of the dimethylsulfoxide reductase (DMSOR) class. Abstract : A new molybdenum complex, [Et4 N]2 [Mo(PPh3 )(mnt)2 –O{Mo(mnt)2 ]·CH2 Cl2 ·½H2 O (1, mnt = maleonitrile dithiolene = S2 C2 (CN)2 ), with unique structural features was synthesized, in which the fragment Mo(PPh3 )(mnt)2 – was attached to another important –OMo(mnt)2 moiety. The structure of1 was formed by the association of both the oxo and desoxo motifs of the dimethylsulfoxide reductase (DMSOR) class of enzymes. This dissymmetrical binuclear complex1 is rare, and it utilized the basic inorganic aspects to accommodate both moieties; under basic conditions, it was converted to (Et4 N)2 [MoO(mnt)2 ] (2 ). Similarly, when treated with PhSH and PPh3, it was completely converted to [Et4 N]2 [Mo(PPh3 )(mnt)2 (SPh)] (3 ) ( J. Am. Chem. Soc., 2006, 128, 4196–4197). The chemistry of1 was analyzed with regard to its synthesis, reactivity, crystal structure, and spectroscopic and photophysical properties. In addition, the results were complemented with DFT calculations.